CONSTITUTIONAL INTERPRETATION AND ITS REFLECTIONS ON CONSTITUTIONAL MUTATION - Simeão, Álvaro Osório do Valle (2020)
The theme of this article is "the constitutional interpretation and its reflections on constitutional mutation". The following problem was investigated: "How can constitutional interpretation interfere with constitutional mutation?". The following hypothesis was considered "the non-observance of principio logical and semiotic limits in constitutional interpretation generates direct impacts on constitutional mutation." The general objective is "to analyze what are the reflexes of constitutional interpretation for constitutional change". The specific objectives are: "to allow a reflection on the art of interpreting the constitution"; "demonstrate the difficulties existing in the interpretative exercise of the constitutional text"; "present the impacts generated by non-compliance with limits on constitutional interpretation." This work is important for an operator of law because it provokes reflection on how much constitutional interpretation directly interferes in professional practice; for science, it is relevant because there is a need to keep alive the debate on constitutional interpretation, as well as to propose a constant reflection on the implications generated by misinterpretations and exacerbated of the constitutional text; adds to society by the fact that constitutional interpretation must be committed to analyzing a set of factors in the incessant search for an interpretation that is more reliable to the Magna Carta and that is closer to the wishes of the people. This is a theoretical qualitative research lasting six months.